Under the mask: The double-edged sword effect of leader self-sacrifice on employee work outcomes - Jiao, Yu-Chen; Wang, Yu-Chen (Frontiers in Psychology, 2023)
Building on attribution theory, this study applied regression analysis and explored the double-edged sword effect of leader self-sacrifice behavior on employee work outcomes, thus revealing the potential negative impacts of such behavior. Specifically, when leadership self-sacrifice was met with low employee authenticity attribution, we found that employees tended to perceive leadership as hypocritical, thus reducing their organizational citizenship behavior. By contrast, when leaders’ self-sacrifice behavior was met with high employee authenticity attribution, employees tended to trust the leader and improve their task performance. Given these findings, we challenge the general scholarly consensus on leadership self-sacrifice behavior, enrich the current literature on leadership self-sacrifice, and emphasize the important role of employee attribution in the relevant leadership process.